Polonocentryzm w twórczości Wincentego Pola - Bryła, Władysława (Idiolekty, 2025)
This paper concentrates on the linguistic features of Wincenty Pol, a poet and academic geographer, who represents domestic Romanticism. The author concludes that Pol’s poetry is Polonocentric in nature and highlights Polish traditions, history, and values significant to Poles during the partitions. Writing in Polish, Pol worked across a variety of genres, including songs, poems, and prayers. His works frequently celebrated Polish landscapes, mountains, rivers, and architectural monuments. By using geographic names, Pol situated the objects of his descriptions within specific temporal and spatial contexts.